A Nonlinear Subdomain and Magnetic Circuit Hybrid Model for Open-Circuit Field Prediction in Surface-Mounted PM Machines - Wu, Lijian; Yin, Hao; Wang, Dong; Fang, Youtong (IEEE transactions on energy conversion, 2019)
The magnetic potential drop in nonlinear iron can be replaced by equivalent current sheets on linear iron edges. Based on this principle, this paper proposes a nonlinear subdomain and magnet circuit hybrid model (SMCHM) for open-circuit field prediction in surface-mounted permanent-magnet machines. The values of current sheets are calculated from a magnetic circuit and used as boundary conditions in the subdomain model. The finite element (FE) validation is performed, which shows the SMCHM can accurately predict the magnetic field distribution and electromagnetic performance as nonlinear FE method does. The accuracy of SMCHM is significantly higher than the conventional subdomain model neglecting a nonlinearity effect, and the computation speed of SMCHM is dramatically faster than the FE model.